Atomistically kinetic simulations of carbon diffusion in ɑ-iron with point defects - Hồ, Ngọc Nam, 1994- (2020)
By using newly-developed Tersoff potential, we have investigated the diffusion properties of carbon in BCC iron for one to three carbon atoms. For single carbon, the fundamental mechanism for diffusion should be from O-site to the 1NN O-site. In case of two carbons, these two atoms tend to form C-C pairs, where one is shifted off the O-site and another is located closely to T-site, with binding energy of -0.224×10-19J. The smallest energy barrier of carbon when diffusing to other position is about 0.702×10-19J. In three-carbon case, the third carbon prefers to bind to the two pre-located carbon atoms in the neighbor cells with a binding energy about -1.057×10-19J. The smallest values of activation energies are about -0.417×10-19J. Moreover, the results of diffusion rates showed the binding ability of carbon atoms: when carbon atoms were inserted into Fe bulk, the formation of large clusters was not a priority because the carbon atoms tend to combine to form a stable C-C pair.